The Influence of Determinant Factors on Safety Behavior for Infusion Installation in Emergency Room Nurses - Dwi Ochta Pebriyanti (Universitas Kadiri, 2024)
Hospitals are unique and complex workplaces, with potential health and safety hazards that cannot be avoided, such as being pricked by needles used by patients. Healthcare Associated (HAIs) is one of the risks faced by health workers and occurs frequently throughout the world with the highest incidence in poor countries and developing countries, WHO shows around 8.7% of 55 hospitals in 14 countries in Europe, the Middle East, and Southeast Asia and the Pacific occur HAIs. The level of work safety knowledge and motivation is most strongly related to work safety behavior. This study aims to analyze the influence of determinant factors on the safety behavior of infusion installation among nurses in the emergency room at Dr. RSUD. Haryoto Lumajang. This research uses quantitative research methods with a cross-sectional research design, sampling technique, namely a total sampling of 21 people. Results: Based on the results of the linear regression test, there is an influence of gender (sig. value 0.004), length of service (sig. value 0.031) and K3 training/socialization (sig. value 0.004) on the safety behavior of infusion installation. The demands of work as a nurse, especially in the ER, which is the first door for patients to enter, where patient safety is prioritized sometimes require nurses to work unsafely.